Utilization Of Bacan Coastal Fishery Port Facilities South Halmahera District - Darmawaty, Darmawaty; Malik, Fikri Rizky; Ahmad, M. Djanib (Agrikan Jurnal Agribisnis Perikanan, 2021)
The purpose of this study is to see the level of utilization of the facilities owned by the Bacan Coastal Fishing Port. The results of this study are expected to be information material for the management and development of the Bacan Coastal Fishing Port. The method used in this research is a descriptive survey method which is a case study. The results show that the utilization rate for the length of the pier is 122%, the utilization rate for the depth of the pond is 35%, the utilization rate for the provision of diesel fuel was 33% and the utilization rate for the provision of ice blocks is 888%. Based on the results of these studies, it can be concluded that the depth of the pond and the provision of diesel fuel at the Bacan Coastal Fishing Port is not optimal, while the utilization rate of the length of the pier and the provision of ice blocks have passed the optimal point so that it is necessary to develop.